The effects of simulated duathlon on multisegment running external and internal load in well-trained triathletes - Rojas-Valverde, D.; Oliva-Lozano, J. M.; Gutierrez-Vargas, R.; Pino-Ortega, J.; Muyor, J. M.; Gomez-Carmona; Gómez-Carmona, C. D. (International Journal of Performance Analysis in Sport, 2023)
Duathlon is a rapidly promoting sport, so it is necessary to identify the factors that influence performance. This study aimed to analyse internal and external loads and the interactions between them during running legs before and after cycling in duathlon. Twenty-three male and female athletes participated in a simulated duathlon (5k-20k-5k). Internal workload was assessed using the rate of perceived exertion (RPE) and heart rate (maximum: HRMAX; average: HRAVG; R-R interval), whereas external workload was assessed using inertial sensors (Player Load by RealTrack, PLRT) attached to six body locations. The results showed that both running legs presented an increasing trend in RPE, HRMAX, and HRAVG throughout the kilometres, while the R-R interval decreased. The PLRT of the upper and lower back, knee, and ankle increased throughout the first running leg but not in the second. The PLRT was greater in the lower body than in the upper body because of energy absorption. RPE was higher in the second running leg than in the first leg. In conclusion, the cycling leg affects the internal and external load between running legs in duathlon. Load monitoring can help coaches understand duathletes` performance and design specific training strategies to reduce fatigue during competition.